Scaffolding lesson report - Bonnewell, Tiffany M. (Kansas State University, 2018)
In the lesson clip shown, students are learning to count rhythms containing rests using the Eastman counting method. The learning target is to prepare students to "count sing" during rehearsals in their advanced choir next school year. During my time at Kansas State University, I have learned several things that have greatly changed the way I conduct a classroom rehearsal. I have begun to pre-teach more, make corrections immediately, and design lessons with more accountability and differentiation.
Keywords: Music; Education; Teaching; Demonstration; Scaffolding